AUTOMATED SHORT ESSAY SCORING AND ITS APPLICATION FOR CHARACTER IMPROVEMENT STUDENT HONESTY - Evi Susilawati; Imamul Khaira (Proceeding International Seminar of Islamic Studies, 2022)
The use of Information and Communication Technology in learning activities often makes it difficult for lecturers to measure student work results whether their work is plagiarized or not. Many students do plagiarism and behave dishonestly in reporting the results of their work. To overcome this problem, an assessment model is needed that is able to see the similarity of student answers. Therefore, it is necessary to apply the Automated Short Essay Scoring (ASES) assessment model. This study is intended to determine the application of the Automated Short Essay Scoring (ASES) assessment model to increase the honesty character of students in the Public Policy course. This research is a classroom action research and is guided by the research concept developed by Kurt Lewin, by carrying out two treatment cycles. This research was applied to students in the seventh grade of the PPKn Study Program, Faculty of Teacher Training and Education (FKIP) of the Islamic University of North Sumatra (UISU) totaling 16 people with four stages of research, namely the planning stage, implementation stage, observation, and reflection. Data collection techniques in this study through observation, interviews, and documentation. The results showed that there was an increase in the honesty character of students in learning Public Policy subjects using the ASES assessment model. Based on the results of this study, it is recommended that lecturers who use Information and Communication Technology-based learning can use Automated Short Essay Scoring (ASES) in providing assessments to students.Keywords: Automated Short Essay Scoring, Honesty Character